Comparison of bipolarity features between art students and other university students (Annals of Medical Research, 2021)
Aim: There is a common belief that creativity and artistic talent/creativity are related to psychopathology. Mood disorders are more prominent in studies about relations between creativity and psychopathology. Also patients may be more productive during mania and hypomania periods of bipolar mood disorder. Considering these data, the purpose of this study was to investigate whether there is a predisposition to bipolar disorder in people with artistic creativity. Materials and Methods: A total of 157 students were selected randomly from the Art department and 157 from different departments including Faculties of Law, Science and Literature and Education. Art students had proven their artistic competence by two stage examination. Groups were compared based on mood disorder questionnaire (MDQ) and bipolarity predisposition factors. SPSS 22.0 was used for statistical analyses. Chi-square analysis was used to compare case-control groups according to demographic characteristics.Results: There were no significant differences between the groups in terms of age, sex, education, smoking, marital status, family history of psychiatric disorder. The number of psychiatric admissions were higher in the students of art (p=0.026). Alcohol-substance use was higher among students of Art (p=0.001). The MDQ scale result was 50.3% positive for Art students and 26.8% positive for students from different departments. MDQ scale, the predisposition of bipolar disorder was found to be significantly higher in Art students.Conclusion: The high prevalence of bipolarity features with MDQ scale in art students supports the relationship between artistic talent / creativity and bipolar disorder.
Keywords: Bipolarity; art; creativity.